2002
DOI: 10.1046/j.1460-9568.2002.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment following status epilepticus in immature rats: time‐course and environmental effects

Abstract: Status epilepticus (SE) has a high mortality and morbidity rate in children. Disturbances in learning and memory are frequently associated with SE although it is not clear when the cognitive deficits occur. If cognitive dysfunction occurs immediately following the seizure, the window of opportunity for therapeutic intervention is limited. The first goal of this study was to determine the timing of cognitive dysfunction following SE in weanling rats. As there is evidence that enriching the environment can impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 86 publications
(82 reference statements)
6
69
0
1
Order By: Relevance
“…Animals were then killed and the brain analyzed for cell loss and synaptic reorganization using previously described scales (Rutten et al, 2002). The nonparametric Mann-Whitney test was used to compare cell loss and Timm scores (ranging from 0 to 5, where 5 is the darkest possible staining) (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Animals were then killed and the brain analyzed for cell loss and synaptic reorganization using previously described scales (Rutten et al, 2002). The nonparametric Mann-Whitney test was used to compare cell loss and Timm scores (ranging from 0 to 5, where 5 is the darkest possible staining) (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that functional outcome and likely QoL may improve over time 15, 18, 22, 23. Promising research in animal models is in the process of identifying biomarkers that can be modulated to minimize long‐term functional impairment 89, 90. Additional comparative effectiveness and interventional trials are underway to provide additional data.…”
Section: Discussionmentioning
confidence: 99%
“…Control group n = 10; Epilepsy group n = 10 impaired cognitive performance when compared with healthy controls (Meador 2002). Annemarieke Rutten et al (2002) reported that impairments in visual-spatial memory were present shortly after SE in immature rats and persisted until adulthood. Impairment of a variety of memory types has been extensively described in TLE patients, including verbal, episodic and spatial working memory (Wieser 2004).…”
Section: Discussionmentioning
confidence: 99%